TCR Signaling in T Cell Memory - Daniels, Mark A.; Teixeiro, Emma (Frontiers in Immunology, 2015)
T cell memory plays a critical role in our protection against pathogens and tumors. The antigen and its interaction with the T cell receptor (TCR) is one of the initiating elements that shape T cell memory together with inflammation and costimulation. Over the last decade several transcription factors and signaling pathways that support memory programming have been identified. However, how TCR signals regulate them is still poorly understood. Recent studies have shown that the biochemical rules that govern T cell memory, strikingly, change depending on TCR signal strength. Furthermore, TCR signal strength regulates the input of cytokine signaling, including pro-inflammatory cytokines. These highlight how tailoring antigenic signals can improve immune therapeutics. In this review, we focus on how TCR signaling regulates T cell memory and how the quantity and quality of TCR-peptide-MHC interactions impact the multiple fates a T cell can adopt in the memory pool.